Primitive Accumulation and the Production of Abstract Space: Nineteenth‐century Mire Reclamation on Gotland. Issue 4 (20th February 2014) - Mels, Tom
Abstract In Henri Lefebvre's work, abstract space entails qualitatively new ways of envisioning and strategically arranging the sites within which capital accumulation and everyday life are to unfold. This paper sets out to delineate how this premise can be profitably used to decipher contested tactics of primitive accumulation. Arguing from a particular case—nineteenth‐century reclamation of mires on the island of Gotland, Sweden—the paper explores how primitive accumulation was made possible through the conjunction of three spatialities, representing three key lines of struggle over abstract space. The abstraction and avowed homogeneity of space was produced and regulated by concurrent ideological maneuvers against customary practice, leveled by scientific discourse, and pursued through a legally endorsed material transformation of nature.